Sound Repetition in Indonesian TikTok Speech: A Phonological–Pragmatic Analysis - Afifah Syazwani Solihin; Otong Setiawan Djuharie (INDO PUBLISHING, 2026)
This study investigates the role of sound repetition in Indonesian TikTok speech through a phonological–pragmatic framework. In contrast to morphological reduplication and syntactic repetition, the repetition observed in TikTok oral discourse operates primarily at the level of sound and prosody, serving as a strategy to emphasize meaning and intensify emotional expression. Employing a qualitative descriptive method, this research analyzes spoken data drawn from Indonesian TikTok videos featuring spontaneous verbal interaction. Selected utterances were transcribed and examined by identifying recurring sound sequences and interpreting their pragmatic functions within specific discourse contexts. The findings indicate that sound repetition predominantly occurs in vowel-based and consonant-based patterns, accompanied by rhythmic timing, accelerated tempo, and consistent pitch contours. Pragmatically, these repetitions function to amplify emotional stance, foreground salient discourse moments, and enhance humorous effects. This study contributes to phonological and pragmatic scholarship by highlighting the significance of sound-based emphasis strategies in digital spoken communication.